Perception of Quality Service Provision in Local Government Authorities in Tanzania: A Citizen Participation Perspective - Muchunguzi, Sospeter (JPAS (Journal of Public Administration Studies), 2023)
Citizen participation is regarded as a process which provides private individuals an opportunity to influence public decisions and has long been a component of the democratic decision making process. The study sought to resolve the puzzle of citizen participation in Tanzania by attempting to decipher why public participation is said to be ample but the quality of health and education services provided is still perceived questionable. The study is conducted within the theoretical lens of the decentralization by devolution model and Stigler’s theory to come up with a more refined approach which envisages that increasing the number of actors in governance may probably help to resolve why decentralization by devolution does not necessarily lead to quality service delivery. The study is basically based on qualitative research design with the aim of seeking to get a deeper information regarding the issue in the two areas under study. The major findings of this study is that in instances where citizens effectively participated there were positive results but in most cases where citizens were not given chance to meaningfully participate dissatisfaction with the kind of social services provided by the government was high. Thus, strengthening local participation is an indispensable ingredient for successful provision of quality services to the citizens. The findings from this article make a valuable contribution towards understanding public participation strategies in both rural and urban areas so as to promote joint decision-making to provide effective and efficient service delivery. Consequently, recommendations are proposed to enhance quality social service provision through effective community engagement.